Fetal Pancake Kidney: Prenatal Diagnosis and Postnatal Follow‐up. (27th February 2020) - Perlman, Sharon; Borovitz, Yael; Bar‐Adon, Sonya; Dekel, Benjamin; Achiron, Reuven; Gilboa, Yinon
Abstract : Bilateral failure of the kidneys to ascend during embryonic life may lead to fusion of the two renal masses, resulting in a round mass known as pancake kidney. Reviewing the literature, we did not encounter any reports of prenatal diagnosis of pancake kidneys. We present 6 cases of a pancake kidney diagnosed prenatally. Extrarenal associated anomalies included an aberrant right subclavian artery, nonvisualization of the uterus, consistent with Mayer‐Rokitansky‐Küster‐Hauser syndrome, and a sequence of early‐onset growth restriction, hypospadias, and syndactyly, suspected as Smith‐Lemli‐Opitz syndrome. On postnatal follow‐up, all infants had a normal renal outcome.